- 1-214-256-5804
- info@tutorpace.com

This can be more clarified by taking suitable relevant problems and solutions.

**Example 1**:-Simplify √-9

**Solution:-**

We can use the rule for simplifying the square root for rewrite imaginary numbers. For solving the problem,

we should know the concept of imaginary number i and we should also be aware about its values.

We know that, square root of -9 = 3.3 which is approximately equal 3 (by neglecting negative sign)

= square root of 9 times square root of -1

= 3 times square root of -1, Here √-1= i, which is Imaginary number)

=3 i

So 3i is the most simplified form of √-9.

**Example 2:- **Simplify (i + 2i) (i)

**Solution:- **

In this case first we need to solve parenthesis and then we need to multiply that

Therefore,

(i + 2i) (i) = (3i) (i) (by combining like terms)

= 3i^{2}

We know that the imaginary number,

The value of i^{2} = -1

Therefore from above,

(i + 2i) (i) = 3i^{2}

= 3 (-1)

= -3

Therefore -3 is the simplified form of (i + 2i) (i).